ADVERTISEMENT

BODMAS Calculator

Enter the expression in the given tab and press the calculate button to find the solution of a given expression.

This will be calculated:
ADVERTISEMENT
ADVERTISEMENT

Is This Tool Helpful?

     

BODMAS Calculator

BODMAS calculator is used to solve difficult mathematical expressions that contain mixed mathematical signs such as addition, subtraction, division, and multiplication.

It follows the BODMAS rule to solve the lengthy expressions and gives answers with detailed steps.

What is the BODMAS rule?

The BODMAS rule is an important rule to evaluate complex expressions more easily and smartly. It solves the arithmetic expression in a sequence to remove the difficulty and ambiguous expression. The BODMAS rule is similar to the PEMDAS rule. The entire form of the “BODMAS” is stated below.

  • B = Brackets or parenthesis
  • O = order or exponent
  • D = division
  • M = multiplication
  • A = addition
  • S = Subtraction

How to evaluate the arithmetic expression using the BODMAS rule?

This rule follows the sequence to solve the expression if one operation is missing then it solves the next operation and in solving the operation gives priority first to that operation which comes first in the expression to move from left to right.

To evaluate the arithmetic expression with the help of the BODMAS rule follow the below instructions.

  • Firstly, solve the brackets or parenthesis present in the mathematical expression.
  • Secondly, solve the order or exponent in the mathematical expression if it’s present in the expression.
  • After that, solve the division and multiplication on a priority base (first come then solve first) to move from left to right.
  • Finally, solve the addition and subtraction to move from left to right.

Here we solved some examples manually to illustrate a BODMAS rule in a better way.

Example 1:

Solve the given expression 7+ (6+3) × 52/5.

Solution:

Step 1: First solve the bracket or Parenthesis.

(6 + 3) = 9

Then the given expression becomes.

= 7 + 9 × 52/ 5

Step 2: Now, solve the exponent term.

52 = 5 × 5

     = 25

Then the equation becomes.

= 7 + 9 × 25 / 5

Step 3: Now, simplify the division and multiplication operation on priority bases from left to right.

= 7 + 9 × 25 / 5

= 7 + 225 / 5

= 7 + 45

Step 4: Lastly, solve the addition and subtraction operation to move left to right.

= 7 + 45

= 52

Thus the answer to a given expression,

7+ (6+3) × 52/5 = 52

Example 2:

Solve the given expression 8 + (8+4) × 42/4 -15 + 34.

Solution:

Step 1: First solve the bracket or Parenthesis.

(8 + 4) = 12

Then the given expression becomes.

= 8 + 12 × 42/ 4 - 15 + 34

Step 2: Now, solve the exponent term.

42 = 4 × 4

     = 16

Then the equation becomes.

= 8 + 12 × 16 / 4 - 15 + 34

Step 3: Now, simplify the division and multiplication operation on priority bases from left to right.

= 8 + 12 × 16 / 4 - 15 + 34

= 8 + 192/ 4 - 15 + 34

= 8 + 48 - 15 + 34

Step 4: Lastly, solve the addition and subtraction operation to move left to right.

= 8 + 48 - 15 + 34

= 56 - 15 + 34

= 41 + 34

= 75

Thus the answer to a given expression,

7+ (6+3) × 52/5 = 75

X
icon
AdBlocker Detected!

To calculate result you have to disable your ad blocker first.